2017
DOI: 10.1080/17435390.2017.1353155
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriomimetic poly-γ-glutamic acid surface coating for hemocompatibility and safety of nanomaterials

Abstract: Poly-γ-glutamic acid (PGA), a major component of the bacterial capsule, is known to confer hydrophilicity to bacterial surfaces and protect bacteria from interactions with blood cells. We tested whether applying a bacteriomimetic surface coating of PGA modulates interactions of nanomaterials with blood cells or affects their safety and photothermal antitumor efficacy. Amphiphilic PGA (APGA), prepared by grafting phenylalanine residues to PGA, was used to anchor PGA to reduced graphene oxide (rGO) nanosheets, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…Besides chemotherapy, and contrastingly to a previous review that covered studies reported from 2012–2014 [97], we found that the most explored therapeutic strategy of GBNs is PTT [5,6,46,50,51,58,59,60,61,62,64,66,69,70,72,73,74,75,76,77,79,86,90,92,93]. In the time frame of that review, chemotherapy was the focus of using GBNs, while in the last 6 years, covered by this systematic review, researchers have shown the appealing role of GBNs in PTT.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Besides chemotherapy, and contrastingly to a previous review that covered studies reported from 2012–2014 [97], we found that the most explored therapeutic strategy of GBNs is PTT [5,6,46,50,51,58,59,60,61,62,64,66,69,70,72,73,74,75,76,77,79,86,90,92,93]. In the time frame of that review, chemotherapy was the focus of using GBNs, while in the last 6 years, covered by this systematic review, researchers have shown the appealing role of GBNs in PTT.…”
Section: Discussioncontrasting
confidence: 89%
“…All 55 studies report the development of GBNs alone [44,45] or often functionalized with different additives [5,6,7,8,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94] for cancer theranostic applications. Each of these studies presented the assessment of the individual role of GBNs either in therapeutic or diagnostic applications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PPGA was synthesized through amide coupling between γ -PGA (50 kDa; BioLeaders, Daejeon, Republic of Korea) and phenylalanine ethylester (Sigma, St. Louis, MO, USA) as described previously 21 . In brief, 10 g of γ -PGA was dissolved in 1 L of 0.3 mol/L NaHCO 3 solution, to which was added 15 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC; Tokyo Chemical Industry Co., Ltd., Tokyo, Japan), followed by stirring for 30 min on ice.…”
Section: Methodsmentioning
confidence: 99%